The Outdoor Chums on a Houseboat; Or, The Rivals of the Mississippi - Allen, Quincy (Salt Lake City, UT : Project Gutenberg, 2011)
"The Outdoor Chums on a Houseboat; Or, The Rivals of the Mississippi" by Quincy Allen is a young adult adventure novel written in the early 20th century. This story follows four college boys known as the Outdoor Chums$1 (BFrank Langdon, Will Milton, Jerry Wallington, and Bluff Masters$1 (Bas they embark on a river journey down the Mississippi. The narrative sets the stage for an exciting summer filled with outdoor adventures, rivalries, and unexpected encounters. At the start of the tale, the friends are buzzing with excitement as Will reveals that his Uncle Felix has invited them to take a houseboat down the river. The situation quickly evolves, and the boys prepare for the adventure ahead, despite having a wistful idea of an extravagant boat. However, the reality is much more modest, which leads to amusing banter among the group. As they set off, they are alert to the potential dangers of the river and unpredictable characters, particularly a mysterious figure named Marcus Stackpole, about whom Uncle Felix has expressed concern. The opening chapters deftly introduce the characters, their camaraderie, and the thrilling elements of youth and adventure, setting the stage for what promises to be a summer filled with challenges and discoveries. (This is an automatically generated summary.)s
Release date is 2011-04-11
Produced by Roger Frank and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Houseboats -- Juvenile fiction; Mississippi River -- Juvenile fiction